Branched polyelectrolyte grafted carbon dots as the high-performance friction-reducing and antiwear additives of polyethylene glycol. (August 2019) - Mou, Zihao; Wang, Baogang; Lu, Hongsheng; Quan, Hongping; Huang, Zhiyu
Abstract: Branched polyethyleneimine (PEI) grafted carbon dots (CDs-PEI0.6-10k ) were facile synthesized by hydrothermal treatments of citric acid and PEI with various molecular weights of 0.6, 1.8 and 10 k. With the aid of protonation and anion exchange (between Cl − and bistrifluoromethanesulfonimide abbreviated as NTf2 - ) processes in aqueous phase, the branched polyelectrolyte grafted CDs (CDs-PEI0.6-10k -NTf2 ) derived from CDs-PEI0.6-10k were gained as the precipitates. The tribological properties of CDs-PEI0.6-10k -NTf2 as the lubricant additives of polyethylene glycol (PEG200) were evaluated. The CDs-PEI0.6-10k -NTf2 exhibited superb friction-reducing and antiwear performances followed the sequence: CDs-PEI10k -NTf2  > CDs-PEI1.8k -NTf2  > CDs-PEI0.6k -NTf2 . Typically, the friction coefficient and wear volume of PEG200 reduced by 53.8% and 79.9%, respectively, when only 0.07 wt% of CDs-PEI10k -NTf2 was introduced. The surface analysis results revealed that a tribochemical reaction film composed of iron compounds (including iron fluorides, sulfates, nitrides, oxides and carbides) and organic compounds containing various elements (such as C, O, N, S and F) should form on the rubbing surfaces lubricated by CDs-PEI10k -NTf2 (0.07 wt%)/PEG200 dispersion. The distinguished friction-reducing and antiwear properties of CDs-PEI10k -NTf2 could be attributed to their nanolubrication effects and the above tribochemical film, i.e. the synergistic lubrication effect of their carbon cores and surface groups. Graphical abstract: Image 1